Brentuximab vedotin and ESHAP is highly effective as second-line therapy for Hodgkin lymphoma patients (long-term results of a trial by the Spanish GELTAMO Group). (18th January 2019) - Garcia-Sanz, R; Sureda, A; de la Cruz, F; Canales, M; Gonzalez, A P; Pinana, J L; Rodriguez, A; Gutierrez, A; Domingo-Domenech, E; Sanchez-Gonzalez, B; Rodriguez, G; Lopez, J; et al.
Abstract: Background: In this work, we assessed the efficacy and safety of brentuximab vedotin (BV) plus ESHAP (BRESHAP) as second-line therapy for Relapsed/Refractory Hodgkin lymphoma (RRHL) to improve the results before autologous stem-cell transplantation (ASCT). Patients and methods: This was a multicenter, open-label, phase I–II trial of patients with RRHL after first-line chemotherapy. Treatment had three 21-day cycles of etoposide, solumedrol, high-dose AraC, and cisplatin. BV was administered at three dose levels (0.9, 1.2, and 1.8 mg/kg) intravenous on day ‒1 to 3 + 3 cohorts of patients. Final BV dose was 1.8 mg/kg. Responding patients proceeded to ASCT, followed by three BV courses (1.8 mg/kg, every 21 days). Main end points for evaluation were maximum tolerable dose and overall and complete response (CR) before ASCT. Results: A total of 66 patients were recruited (median age 36 years; range 18–66): 40 were primary refractory, 16 early relapse and 10 late relapse. There were 39 severe adverse events were reported in 22 patients, most frequently fever ( n = 25, 35% neutropenic), including 3 deaths. Grade 3–4 hematological toxicity presented in 28 cases: neutropenia ( n = 21), thrombocytopenia ( n = 14), and anemia ( n = 7). Grade ≥3–4 extrahematological adverse events (≥5%) were non-neutropenic fever ( n = 13) and hypomagnesaemia ( n = 3). Sixty-four patients underwent stem-cell mobilization; all collected >2×10e6/kg CD34+ cells (median 5.75; range 2.12–33.4). Overall response before transplant was 91% (CI 84% to 98%), including 70% (CRs 95% CI 59% to 81%). 60 patients were transplanted with no failure engraftments. Post-transplant response was CR in 49 patients (82% CI 73% to 91%) and partial responses in six (10% CI 5% to 15%). After a mean follow-up of 27 months, the 30-month time to treatment to failure was 74% (95% CI 68% to 80%), progression-free survival 71% (95% CI 65% to 77%), and overall survival 91% (CI 84% to 98%). Conclusion: BRESHAP looks a safe and effective pre-transplant induction regimen, does not jeopardize transplant and allows long-term remissions and survival.